Agatha Christie's partners in crime [videorecording (DVD)] - Raine, Jessica, 1982-; Walliams, David, 1971-; Peters, Clarke; Krige, Alice, 1954-; Christie, Agatha, 1890-1976; Christie, Agatha, 1890-1976 (Acorn ; RLJ Entertainment, Inc., 2016)
An ordinary married couple gets caught up in international intrigue and discovers that they have a knack for crime solving in this charming detective series.